Coping with stress related to illness – the modern theoretical concepts - Kozaka, Joanna (Psychoonkologia, 2010)
The aim of the study was to introduce modern concepts of coping with stress in cancer. In analysis of the experiences of people with cancer, stress should be recognized in a systemic manner as a complex of environmental, situational and subjective elements, as well as dispositional and processual ones. Currently the transaction approach is the most widely considered (Lazarus and Folkman). It is supplemented with salutogenetic construct created by Antonovsky, which is the sense of coherence. The important idea is the Hobfoll’s theory of resources conservation, which makes an important contribution to understanding the situation of cancer patients. Moreover, there is an interesting approach to dealing with stress presented by Schwarzer, who focuses on future-oriented factors.